Broken images. "Auschwitz", nostalgia and modernity. The reception of the Holocaust in popular culture - Kaźmierczak, Marek (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2011)
Broken images. "Auschwitz", nostalgia and modernity. The reception of the Holocaust in popular culture The reception of the Holocaust in popular culture is like a set of the broken images of the past. There are fluent differences between fiction and reality, beetween texts and facts, between knowledge and ignorance. This article concerns the forms of the influence of poplar culture on the representations of the Holocaust. Broken image can reveal a part of same event, the same fact. There are intellectual and axiological challenges between revealing and abusing the “Auschwitz” in the contemporary texts of culture. There are three main parts of the article: The contexts of the terms, Opened arguments and How instrumentally where are described the mechanisms of reduction, instrumentalization and mediatization of the reception of the Holocaust.